(untitled) (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
Golden snail (Pomacea canliculata L.) is an important pest on rice plants so that there is a decrease in rice production, golden snails can be controlled with botanical insecticides. One of the botanical insecticides that can be used to control gold snail pests is soursop leaf extract. This study aims to determine the effect of soursop leaf extract on golden snails and the optimal concentration of soursop leaf extract to control golden snails. This research was conducted in April June The study was conducted using a completely randomized design (CRD) with 5 treatments which were repeated 4 times. Based on the results of the study after the application of soursop leaf extract on golden snails (P. canaliculata) after one day of application there were no signs of gold snail mortality, the mortality rate of golden snails occurred on the seventh day of rice which had differences in each concentration where, P1 with a concentration of 40% can cause 66,66% mortality. P2 with a concentration of 50% causes 70% mortality. P3 with a concentration of 60% caused 91,66% mortality. P4 at a concentration of 70% can cause up to 100% mortality. While P0 or controls did not experience mortality because they were not given the extract. Based on each concentration the number of mortality in each treatment isdifferent.The conclusion thatcan be drawn from this study is thatsoursop leaf extract with a concentration of 70% can kill the mortality of golden snails up to 100%.